Embodiment, agency, unmet need: Young women's experiences in the use and non-use of contraception in Khayelitsha, South Africa. Issue 6 (3rd June 2022) - Hayer, Sarena; DiClemente, Kira; Swartz, Alison; Chihota, Zipho; Colvin, Christopher J.; Short, Susan E.; Harrison, Abigail
ABSTRACT: Globally, high rates of unintended pregnancy occur despite widespread distribution of modern contraceptive methods, reflecting the complexity of individual contraceptive use. The concept of unmet need provides a framework for addressing the gap between women's desire to prevent pregnancy and the ability of health services to meet women's contraceptive needs. Through in-depth interviews in Khayelitsha, South Africa, we examine 14 young women's experiences with contraception, interrogating how and why reproductive intentions and outcomes often differ markedly. Three main themes were identified and explored. First, unintended pregnancies were common in our sample, despite high knowledge about contraceptive options and availability of multiple methods. Second, women's contraceptive preferences are strongly shaped by concerns with side effects and other embodied experiences, leading to pivotal moments of method-switching or cessation of contraceptive use. Third, using contraception provides participants with the potential for purposeful and self-directed action. These enactments of agency though, occur within intimate and familial relationships, where gendered expectations of the participants' choices ultimately shape both method preference and use. These findings demonstrate the need for an understanding of women's lives and narratives as the basis for understanding complex health behaviours such as contraceptive use.